Réflexion et méthodologie: autour d’une prise d’empreinte en papier - Cyril Benoît; Florence Lagger; Noé Terrapon (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
A stone recumbent figure from the end of the 13th century has been discovered in the chancel of the Notre Dame basilica in Fribourg. In this article, the ethical questions related to the replication or casting of cultural heritage witnesses are underscored. The authors raise their skepticism about reproductions and consider molds as a simple documentary support. The discovered figure has been lifted from its original location. A mold has been applied for documentary purposes. The molding method has been inspired by the epigraphist’s method: a stamping with blotting paper. This technology has been adapted to the current circumstances. The mold removal has been enhanced by adding cyclododecan under an overall compound made of plaster paper, expanded foam and wooden structure.